40Lateral left ventricular lead position and long interlead electrical delay predict long-term all-cause mortality in cardiac resynchronization therapy patients. (18th June 2020) - Behon, A; Schwertner, W R; Merkel, E D; Kovacs, A; Kutyifa, V; Lakatos, B; Zima, E; Geller, L; Kosztin, A; Merkely, B
Abstract: Background: There is limited data on the association of left ventricular (LV) lead position and long-term clinical outcome in patients after cardiac resynchronization therapy (CRT). Purpose: We evaluated the mid-term echocardiographic response and long-term all-cause mortality of patients who underwent CRT implantation by LV lead non-apical positions and further characterized them by right to left ventricular, interlead electrical delay (IED). Methods: In our retrospective registry patients after CRT implantation between 2000 and 2018 were registered. Those with non-apical LV lead location were classified into anterior (n = 111), posterior (n = 652), and lateral (n = 1373) positions. Primary endpoint was all-cause mortality assessed by univariate- and Cox multivariate analyses. Secondary endpoint was echocardiographic response within 6 months after CRT implantation. Results: From 2136 patients 1180 (55.2%) reached the primary endpoint during the mean follow up time of 4.5 years. Univariate analysis showed patients with lateral position had significantly better outcome compared to others (HR 0.80; 95% CI: 0.71-0.90; p < 0.01), which was also confirmed by Cox multivariate analysis (HR 0.69; 95% CI: 0.50-0.93; p = 0.02) after adjusting for relevant clinical covariates such as IED and LBBB. The median value of IED was 106 (89/124) ms in the total patient cohort, which was significantly longer in the lateral group [anterior 80 (60/100) ms vs. lateral 110 (91/128) ms vs. posterior 100 (85/120) ms; p< 0.01]. When echocardiographic response was further evaluated in patients with lateral position, those with an IED longer than 110 ms (ROC AUC 0.64, 95% CI: 0.54-0.74; p = 0.01) showed the greatest benefit within 6 months. Conclusions: After CRT implantation the most beneficial outcome was associated with lateral left ventricular lead location, moreover the greatest echocardiographic response was found when interlead electrical delay was longer than 110 ms in this group.